UPAYA MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS DENGAN METODE PEMBERIAN TUGAS TEMA ALAM SEMESTA DI SDN 29 SORONG - Bontong, Adrianus Tambing; Sampe, Keristina; Fatmawati, Fatmawati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to evaluate the effectiveness of implementing an assignment method with the theme of the universe in improving language skills at SDN 29 Kabupaten Sorong. Through the classroom action research method, two cycles of observation take place to assess the improvement in interest, motivation, and the reading and writing skills of Group B children. The research results show that applying this method successfully increases children's interest and motivation in language learning and significantly improves their reading and writing skills. The universe theme proves to be the right choice to stimulate children's curiosity and motivate them to be more active in reading and writing activities. In addition, this approach helps children understand new concepts in a more engaging and enjoyable way. Thus, this research contributes to developing language learning strategies in schools and shows that a thematic approach can be an effective solution for improving the quality of learning in similar educational institutions. The implications of this research also apply to the development of a more interactive thematic-based curriculum that focuses on the needs and characteristics of children.